The Impact of Immersive and Non-Immersive Virtual Reality Trends in Sensorimotor Recovery of Post-Stroke Patients-A Meta-Analysis - Rizvi, Jaza; Farooqui, Sumaira Imran; Khan, Abid; Soomro, Bashir Ahmed; Hassan, Batool (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Virtual Reality (VR) is an approach in stroke rehabilitation with ever-improving technological advancement for targeted motor rehabilitation by providing a user interface in a simulated environment with proprioceptive and visual feedback. This meta-analysis intended to evaluate the impact of immersive and non-immersive VR-based interventions compared to conventional rehabilitation in sensorimotor recovery following stroke. Randomized Controlled Trials based on the impact of VR, either immersive or non-immersive type in comparison to conventional rehabilitation on post-stroke patients (>18 years) sensorimotor recovery were searched on six databases including Google Scholar, PEDro, MEDLINE, Cochrane Library, EMBASE, and Web of Science from August to November 2020. A total of 17 randomized controlled trials on VR based intervention showed significant improvement in sensorimotor recovery following a stroke in overall FMA outcomes in comparison to the control group with pool effects in terms of SMD in a random effect model showed an impact of 0.498 at 95% CI (p<0.001) depicts a moderate effect size. An immersive and non-immersive emerging VR trend appears to be a promising therapeutic tool in sensorimotor recovery following stroke.